An Intricate Balance: The Challenge of Caring During COVID-19 While Maintaining High Student Expectations - Gullo, Gina (Journal of Interdisciplinary Studies in Education, 2021)
Understanding the challenges faced by graduate students during the COVID-19 pandemic is difficult for professors aiming to maintain high expectations of students. This essay explores the balance between caring for and challenging students in the face of their needs and limitations during social distancing.